Analyses of the relationships among biofilm activity, antibiotic resistance and expressions of SHV, TEM, CTX and IntI in Klebsiella pneumoniae (Annals of Medical Research, 2021)
Aim: Klebsiella pneumoniae as an opportunistic pathogen is responsible for nosocomial, urinary tract infections, pneumonia, bacteremia, liver abscesses, and respiratory and blood infections in patients. The aim of our study is to examine the antibiotic sensitivity, expression levels of IntI, TEM, SHV and CTX genes, which play a role in multidrug resistance, biofilm formation and even the relationships among them. Materials and Methods: Identification was implemented by carrying out the VITEK2 system and phenotypic confirmation of the ESBL producing isolates by using a combined disc test. Antibiotic sensitivity was implemented by disc diffusion method and microdilution methods toward various antibiotics. Furthermore, biofilm formation was examined through microtitration plate method. Results: The expressions of IntI, TEM, SHV and CTX were implemented in qRT-PCR. 19 were susceptible to all antibiotics, 17 were ESBL (+) and 16 were carbapenem-resistant among 52. The expression of these genes was upregulated in ESBL (+) strains and produced biofilm and the expression of these genes was upregulated, too. Conclusion: The results of the study revealed the potential role of the mentioned genes in biofilm formation and antibiotic resistance, enabling the development of new drugs. Further studies will be essential so as to determine when or how these systems are included in antibiotic resistance and biofilm formation.